Euro-currency market as recycling medium - Helmut Mayer (Intereconomics, 1975)
During the past year the Euro-currency market played a very large role in bridging over the oil-induced payments imbalances. In the interest of international monetary stability this market should now move somewhat away from the centre of the stage and leave the main responsibility for the recycling of oil funds to the official financing mechanisms.
Keywords: 330; Monetary Policy